The influence of academic adminisrative service quality on student satisfaction: Evidence from undergraduate students a Universitas Kristen Maranatha - Syaepudin Syaepudin; Tengku Ine Hendriana; Rini Ratnaningsih; Ervie Nur Afifa Mukhlis; Tuti Sulastri (Trigin Publisher, 2026)
The quality of academic administrative services plays a significant role in shaping students’ educational experiences and satisfaction levels. As one of the key indicators of institutional performance, effective academic administration contributes to the overall quality of higher education services. Despite extensive research on service quality and student satisfaction, limited studies have specifically examined academic administrative services within creative higher education programs, where administrative support is closely linked to students' academic experiences and learning processes. This study investigates the effect of academic administrative service quality on student satisfaction in the Visual Communication Design Undergraduate Program at Universitas Kristen Maranatha, Indonesia. A quantitative approach was employed using questionnaire-based data collection. The respondents consisted of 100 active undergraduate students representing the 2020–2023 cohorts. Data were analyzed using descriptive statistic validity and reavility tests, normality testing, and simple linear regression analysis The findings reveal a strong and statistically significant relationship between academic administrative service quality and student satisfaction. The coefficient of determination indicates that service quality explains 86.8% of the variation in student satisfaction. These findings highlight the strategic role of academic administrative services in enhancing student experiences and provide empirical evidence to support service quality improvement initiatives in higher education institutions, particularly in specialized academic programs. Therefore, the study confirms that improvements in academic administrative services contribute positively to higher levels of student satisfaction.